2000
DOI: 10.1143/jjap.39.5623
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Jumping and Dropping Phenomena of Piezoelectric Transducers using the Electrical Equivalent Circuit Constants at High Vibration Amplitude Levels

Abstract: This paper presents an analysis of the jumping and dropping phenomena of piezoelectric transducers, using the electrical equivalent circuit constants at high vibration amplitude levels of resonance based on the electrical transient response technique. The calculated frequency characteristics well simulated the measured ones driven by a constant voltage source. It is clarified from the results that the jumping and dropping phenomena are caused mainly by the nonlinear behavior of the elastic constant at high vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 5 publications
0
40
0
Order By: Relevance
“…The authors speculate that the nonlinearity of the vibration velocity in the transducer with a large applied voltage, which increases the mechanical loss of the vibration system, 4,5) is one of the main reasons for the low efficiency of the prototype motor, and the optimization of design for excitation of the desired vibration modes and control, and how the electrical driving parameters are chosen should be considered for a more effective operation of the motor. mental equipment, and also Dr. James R. Friend, a research Phase between Two Input Currents (rad) No-load Speed (rad/s) Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The authors speculate that the nonlinearity of the vibration velocity in the transducer with a large applied voltage, which increases the mechanical loss of the vibration system, 4,5) is one of the main reasons for the low efficiency of the prototype motor, and the optimization of design for excitation of the desired vibration modes and control, and how the electrical driving parameters are chosen should be considered for a more effective operation of the motor. mental equipment, and also Dr. James R. Friend, a research Phase between Two Input Currents (rad) No-load Speed (rad/s) Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced Bode plot techniques were developed from the basic constant voltage versus frequency sweep; this included constant current and constant velocity interrogated locally on transducer (Uchino et al, 2003, Ural et al, 2009, with added up and down directional frequency sweeps to quantify hysteresis effects (Umeda et al, 2000). Selected transducers with known "good" and known "bad" process control were studied, and a linear coupled-field FEA model was correlated to the "good" transducer.…”
Section: Research Summarymentioning
confidence: 99%
“…Various authors have investigated the nonlinear response characteristics of power ultrasonic systems [3][4][5]. In all these studies, the nonlinear behaviour of piezoceramics was found at the foundation of the nonlinearity of the investigated systems.…”
Section: B Full Titanium Hornmentioning
confidence: 99%
“…It is, in fact, well-known that the PZTs behave nonlinearly even when they are driven at relatively low voltages [6]. Experimental methods to remove the thermal effects due to PZT internal losses on the response characteristics of ultrasonic devices have been previously proposed [4][5]. Through these methods the effect of the change of PZT elastic compliance with power on the softening response of power transducers could be quantified.…”
Section: B Full Titanium Hornmentioning
confidence: 99%
See 1 more Smart Citation